أثر التجارة الرقمية على التنمية المستدامة - شبرو سفيان; محمد الحبيب رزاق زوازي; محمد الناصر شايع (university of eloued جامعة الوادي, 2025)
"هدفت الدراسة إلى تحليل أثر التجارة الرقمية على أبعاد التنمية المستدامة (الاقتصادية، الاجتماعية، والبيئية) في دول مجموعة البريكس (البرازيل، روسيا، الهند، الصين، جنوب إفريقيا) خلال الفترة 2010–2023. سعت إلى تحديد مدى مساهمة الصادرات والواردات الرقمية في تعزيز النمو الاقتصادي، وتحسين مؤشرات التنمية البشرية وتقليل الانبعاثات الكربونية، مع مراعاة الفروق الهيكلية بين الدول. حيث اعتمدت الدراسة على منهجية تحليل بيانات البانل (Panel Data) لدمج البيانات المقطعية والزمنية، باستخدام برنامج Eviews13. شملت المتغيرات المستقلة: صادرات وواردات الخدمات الرقمية (كنسبة من إجمالي تجارة الخدمات) ومؤشر جاهزية التكنولوجيا الرائدة (FTRI)، بينما تمثلت المتغيرات التابعة في الناتج المحلي الإجمالي (GDP) للبعد الاقتصادي ومؤشر التنمية البشرية (HDI) للبعد الاجتماعي، وكثافة الكربون (CO2) للبعد البيئي. جُمعت البيانات من مصادر دولية مثل البنك الدولي والأونكتاد، مع تطبيق اختبارات تحديد النموذج الملائم. أظهرت النتائج أن صادرات الخدمات الرقمية ساهمت إيجابيًا في نمو الناتج المحلي الإجمالي (بنسبة 0.087% لكل زيادة 1% في الصادرات)، بينما ارتبطت واردات الخدمات الرقمية بتأثير سلبي(-0.246%) يعزى إلى الاعتماد على التقنيات الأجنبية. في البعد الاجتماعي، سجلت الجاهزية التكنولوجية (FTRI) تأثيرًا إيجابيًا قويًا على مؤشر التنمية البشرية (0.455 نقطة لكل تحسن بمقدار نقطة واحدة)، بينما أظهرت الصادرات الرقمية تأثيرًا سلبيًا طفيفًا (-0.0028 نقطة) بسبب تركيز فوائدها على فئات محددة. على الصعيد البيئي ساهمت الصادرات الرقمية في خفض الانبعاثات الكربونية (-0.0049%) عبر التحول نحو قطاعات أقل استهلاكًا للطاقة، في حين زادت الواردات الرقمية الانبعاثات (+0.0027%) لارتباطها ببنى تحتية مكثفة الطاقة. هذه النتائج تؤكد الحاجة إلى سياسات متكاملة لتعظيم إيجابيات التجارة الرقمية وتخفيف سلبياتها، مع مراعاة السياقات الوطنية المختلفة. "The study aimed to analyze the impact of digital trade on the dimensions of sustainable development (economic, social, and environmental) in BRICS countries (Brazil, Russia, India, China, and South Africa) during the period 2010–2023. It sought to determine the contribution of digital exports and imports to enhancing economic growth, improving human development indicators, and reducing carbon emissions, while accounting for structural differences among these nations. The study employed a panel data analysis methodology to integrate cross-sectional and time-series data, utilizing the Eviews13 software to estimate fixed and random effects regression models. Independent variables included digital service exports and imports (as a percentage of total service trade) and the Frontier Technology Readiness Index (FTRI). Dependent variables encompassed GDP (for the economic dimension) the Human Development Index (HDI) (for the social dimension), and carbon intensity (CO2) (for the environmental dimension). Data were sourced from international repositories such as the World Bank and UNCTAD, with model suitability tests (e.g., Breusch-Pagan and Hausman tests) applied to ensure robustness. The findings revealed that digital exports positively contributed to GDP growth (0.087% increase per 1% rise in exports), whereas digital imports exhibited a negative association (-0.246%), attributed to reliance on foreign technologies. For the social dimension, technological readiness (FTRI) showed a strong positive impact on HDI (0.455 points per unit improvement), while digital exports had a marginal negative effect (-0.0028 points), likely due to uneven distribution of benefits. Environmentally, digital exports reduced carbon emissions (-0.0049%) by shifting toward less energy-intensive sectors, whereas imports increased emissions (+0.0027%) due to energy-intensive infrastructure demands. These outcomes underscore the necessity for integrated policies to maximize digital trade’s advantages, mitigate its drawbacks, and address country-specific contexts."
ماستر علوم تجارية
Keywords: التجارة الرقمية; التنمية المستدامة; مجموعة البريكس.; Digital trade; sustainable development; in BRICS countries.